UKRVO SPECTRAL PHOTOGRAPHIC ARCHIVE OF VARIABLE STARS - Zolotukhina,, A. V.; Pakuliak, L. K.; Vavilova, I. V.; Kaminsky, B. M. (Одеські астрономічні публікації, 2020)
The overview of the content of an Archive of the spectral photographic observational data stored at the MAO NAS of Ukraine in 1965–1985 is presented. Being the part of the UkrVO Joint Digitized Archive, this archive contains of 50,000 spectra of mostly variable stars. The spectral photographic material (glass astroplates) was obtained by the 70-cm reflector AZT-2 (MAO NAS of Ukraine, Kyiv), 60-cm Zeiss telescope at the Mount Ter- skol (North Caucasus, Russia), and 1-m telescope at the Mount Sanglok (Institute of Astrophysics, Tajikistan) equipped with spectrographs UAGS with a set of gratings to obtain dispersions in the range of 29…167 A/mm of the wavelengths 3500…6800 AA. There is also data related to the observations by the Double Short Astrograph (MAO NAS of Ukraine) with a pre-objective prism to monitor Nova Cygni 1975 in the initial stage of outburst. Almost all the spectra are calibrated with the 9-step attenuator and comparison spectra for the wavelength scale. We discuss observational programs (aims, instruments, results), in frame of which this archive was accumulated, as well as key principles for digitizing spectra and their pro- cessing by modern tools of virtual observatory software.